TRPV4 Complexes With the Na+/Ca2+ Exchanger and IP3 Receptor 1 to Regulate Local Intracellular Calcium and Tracheal Tension in Mice - Zhang, Jie; Wei, Yuan; Bai, Suwen; Ding, Shenggang; Gao, Huiwen; Yin, Sheng; Chen, Shuo; Lu, Jinsen; Wang, Haoran; Shen, Yonggang; Shen, Bing; Du, Juan (Frontiers in Physiology, 2019)
Intracellular Ca2+ is critical for regulating airway smooth muscle (ASM) tension. A rapid rise in the intracellular Ca2+ concentration ([Ca2+]i) of ASM cells is crucial for modulating the intensity and length of the ASM contraction. Because this rapid increase in [Ca2+]i largely depends on the balance between Ca2+ released from intracellular Ca2+ stores and extracellular Ca2+ entry, exploring the mechanisms mediating Ca2+ transport is critical for understanding ASM contractility and the pathogenesis of bronchial contraction disorders. Transient receptor potential vanilloid 4 (TRPV4) is a highly Ca2+-permeable nonselective cation channel that mediates Ca2+ influx to increase [Ca2+]i, which then directly or indirectly regulates the contraction and relaxation of ASM. The [Ca2+]i returns to basal levels through several uptake and extrusion pumps, such as the sarco(endo)plasmic reticulum Ca2+ ATPase and inositol 1,4,5-trisphosphate receptors (IP3Rs), the plasmalemmal Ca2+ ATPase, and the plasma membrane Na+/Ca2+ exchanger (NCX). Thus, to further understand ASM tension regulation in normal and diseased tissue, the present study examined whether an interaction exists among TRPV4, IP3Rs, and NCX. The TRPV4-specific and potent agonist GSK1016790A increased [Ca2+]i in mouse ASM cells, an effect that was completely blocked by the TRPV4-specific antagonist HC067047. However, GSK1016790A induced relaxation in mouse tracheal rings precontracted with carbachol in vitro. To determine the mechanism underlying this TRPV4-induced relaxation of ASM, we blocked specific downstream molecules. We found that the GSK1016790A-induced relaxation was abolished by the NCX inhibitors KB-R7943 and LiCl but not by specific inhibitors of the Ca2+-activated large-, intermediate-, or small-conductance K+ channels (BKCa, IK, and SK3, respectively). The results of co-immunoprecipitation assays showed an interaction of TRPV4 and IP3R1 with NCXs. Taken together, these findings support a physical and functional interaction of TRPV4 and IP3R1 with NCXs as a novel TRPV4-mediated Ca2+ signaling mechanism and suggest a potential target for regulation of ASM tension and treatment of respiratory diseases, especially tracheal spasm.